PHYSICAL FITNESS STATUS ANALYSIS OF MADRASAH ALIYAH ABU DARRIN FUTSAL ATHLETE IN KENDAL BOJONEGORO - riadlus sholihin, riadlus sholihin; dewi, ratna candra (Jurnal Kesehatan Olahraga, 2019)
This study was carried out because of the lack of public attention about his own physical needs and not yet known, The purpose of this study was to increase public attention about his own physical needs. This study was to determine the level of physical fitness of the Futsal Extracurricular MA Abu Darrin player, this physical fitness studyinstrument using the MFT test, the studysubjects used were 20 players. The type of studyused in this study is quantitative studywith a descriptive method approach. Based on the studycarried out by using the MFT test on extracurricular football players in Abu Darrin Aliyah Madrasah 16-18 years old, the majority of them showed a moderate category of 80%, a category of less than 15%, and less than 5%. The results of the study, physical fitness function to improve one's ability to activities so that they can carry out their activities to the maximum to get better results.